Legal Protection for MSME Traders in Indonesia: A Theoretical Study in the Perspective of Economic Law and Consumer Protection - Fitri Fitri (PT. Batari Edu Calya, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have a vital role in the Indonesian economy, contributing more than 60% to GDP and absorbing 97% of the workforce. However, despite this significant contribution, MSME actors still face various legal challenges, including a lack of contractual protection, limited access to financing, and low legal literacy. This study aims to analyze the effectiveness of legal protection for MSME traders from two primary perspectives: economic law and Consumer Protection. The research method used is normative law (normative juridical), by examining laws and regulations, legal doctrines, and related academic literature. The primary legal materials analyzed include Law Number 20 of 2008 concerning MSMEs, Law Number 8 of 1999 concerning Consumer Protection, and other relevant regulations. The results show that although a normative legal framework is available, its implementation and effectiveness are still not optimal. From an economic law perspective, complex bureaucracy and high litigation costs hinder MSMEs from obtaining legal certainty, thereby creating detrimental uncertainty. Meanwhile, from a consumer protection perspective, MSME actors are faced with new challenges in the digital era, such as personal data protection and intellectual property rights, which they often do not understand. In conclusion, concrete steps are needed from the government and stakeholders to increase legal protection for MSMEs. The recommendations submitted include simplifying regulations, increasing legal literacy, facilitating alternative dispute resolution, and adapting regulations to digital dynamics. This research is expected to make a theoretical contribution to economic law and become the basis for policy formulation that is more in favor of MSMEs, in order to strengthen business sustainability and the foundation of the national economy.